2020
DOI: 10.1111/jphp.13342
|View full text |Cite
|
Sign up to set email alerts
|

HWL-088, a new and highly effective FFA1/PPARδ dual agonist, attenuates nonalcoholic steatohepatitis by regulating lipid metabolism, inflammation and fibrosis

Abstract: Objectives Nonalcoholic fatty liver (NAFLD), a chronic progressive liver disease, is highly correlated with pathoglycemia, dyslipidemia and oxidative stress. The free fatty acid receptor 1 (FFA1) agonists have been reported to improve liver steatosis and fibrosis, and the peroxisome proliferator-activated receptor d (PPARd) plays a synergistic role with FFA1 in energy metabolism and fibrosis. HWL-088, a PPARd/FFA1 dual agonist, exerts better glucose-lowering effects than the representative FFA1 agonist TAK-875… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Thus, the effect of ICS II on lipid metabolism were explored, and we found that ICS II efficiently regulated lipid metabolism and reversed the excessive accumulation of fat in liver of db/db mice. In addition, glucose and lipid abnormalities are important factors, resulting in the progression of β cells dysfunction or pancreatic islets destruction [ 31 , 32 , 33 ]. Our findings indicated that ICS II significantly improved structure of pancreas and restored the numbers of β cells in db/db mice, which further confirmed that ICS II was potently against T2DM, and its possible underlying mechanism is worth investigating in depth.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the effect of ICS II on lipid metabolism were explored, and we found that ICS II efficiently regulated lipid metabolism and reversed the excessive accumulation of fat in liver of db/db mice. In addition, glucose and lipid abnormalities are important factors, resulting in the progression of β cells dysfunction or pancreatic islets destruction [ 31 , 32 , 33 ]. Our findings indicated that ICS II significantly improved structure of pancreas and restored the numbers of β cells in db/db mice, which further confirmed that ICS II was potently against T2DM, and its possible underlying mechanism is worth investigating in depth.…”
Section: Discussionmentioning
confidence: 99%